(3GdEYdGe HSfJg Ydjg GdSdGes - (3oenZrdWGj Hf nbpdjL Hf YHO Gddg GdHcLQj GdeUQj GdMcQj GdMfaj, CHh YHO Gddg, YdGA GdOjf , J (B762 (3g` s; (3eMeO Hf jRjO GdQHYj GdbRhjfj, CHh YHO Gddg, GHf eGLI,J (B273 (3g` s
(3ChdgG (B:s
(3jHOC HHGH JMJ cd TYQg LfGjI s
(3BNQgG (B:s
(3hjfJgi HMOjK Gf GdfHi Udi Gddg Ydjg hSde ESJTGQ GdfGS deG jLeYge ddUdGI aPcQhG GdHhb acQgg ef GLd GdjghO s
(3GdejcQhajde Hg Jda HSjWs
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdMOjK h GdeUWdMs